Parental stress and parentsa profiles among parents of children with learning disabilities in Abuja, Nigeria - Olabisi, Akinola Patrick; Ahmad, Sa’odah; Mansor, Mariani; Daud, Mohd Najmi (Human Resource Management Academic Research Society, 2022)
Parental stress is an emotional challenge that troubles parents of children with learning disabilities in the process of caring for their children. This study examined the difference in parental stress among parents of children with learning disabilities in Abuja, Nigeria according to the parents’ profiles. A cross-sectional design was employed to gather the data for this study in the six Area Councils of the Federal Capital Territory (FCT) in Abuja, Nigeria. The study employed a multistage clustered random sampling technique to sample 314 parents of children with learning disabilities who send their children to the Inclusive Basic Primary Schools. Parental stress was measured using the Parental Stress Scale (PSS, Berry and Jones, 1995). The Cronbach’s alpha reliability was 0.83. The results showed a significant difference in parental stress according to the parents’ age group [F (4, 309) = 8.583, p = .000] and the parent's level of income [F(4, 309) = 4.339, p = .014]. Thus, to be effective, the formulation of relevant policies, interventions, support programs, and services for the parents of children with learning disabilities should give due consideration to the age and level of income of the parents.